The Cell Method for Electrical Engineering and Multiphysics Problems: An Introduction - Alotto, Piergiorgio (Lecture Notes in Electrical Engineering, 2013)
This book describes the main components of the cell method technique: space-time discretization, problem formulation, solution and representation of the resulting physical fields. Offers solved problems in electromagnetism, elasticity and thermo-elasticity.